2014
DOI: 10.1242/dev.098392
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator complex: a master coordinator of transcription and cell lineage development

Abstract: Mediator is a multiprotein complex that is required for gene transcription by RNA polymerase II. Multiple subunits of the complex show specificity in relaying information from signals and transcription factors to the RNA polymerase II machinery, thus enabling control of the expression of specific genes. Recent studies have also provided novel mechanistic insights into the roles of Mediator in epigenetic regulation, transcriptional elongation, termination, mRNA processing, noncoding RNA activation and super enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
161
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(165 citation statements)
references
References 155 publications
3
161
0
1
Order By: Relevance
“…In line with the suggested involvement of MED13L in neural crest, 13 and consequently in the development of the facial mesenchyme, there is the presence of cleft palate in our patient 1, most likely.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In line with the suggested involvement of MED13L in neural crest, 13 and consequently in the development of the facial mesenchyme, there is the presence of cleft palate in our patient 1, most likely.…”
Section: Discussionsupporting
confidence: 85%
“…Different subunits can have gene-and tissue-specific functions and several of them have already been demonstrated to be involved in neurodevelopmental processes, and to be associated to ID. 13 Specifically, heterozygous missense variants in MED13L were initially associated with dextro-looped transposition of the great arteries (dTGA), 7 while a balanced translocation t(12;17) disrupting the gene (breakpoint between exons 1 and 2) has been reported as responsible also for ID. In a large study on consanguineous families with cognitive impairment, a different homozygous missense variant was identified, but no information about the associated clinical phenotype was provided.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of SEs and seRNAs upon Activation of TLR4. Previous genome-wide studies have demonstrated that SEs are closely correlated with key developmental genes (12,13,39). To explore SEs and their associated genes as targets of ligand signaling, we examined the regulation of seRNAs following LPS activation of the TLR4 pathway.…”
Section: Resultsmentioning
confidence: 99%
“…auxin response | Mediator complex | CDK8 kinase module | lateral root formation M ediator is a multiprotein complex that relays integrated information from transcriptional factors to RNA polymerase II (RNAPII) (1)(2)(3). Mediator consists of ∼25-30 subunits, which are organized into three modules forming the core Mediator (head, middle, and tail) and the dissociable CDK8 kinase module (CKM) (3,4).…”
mentioning
confidence: 99%
“…Email: ma-furut@agr.nagoya-u.ac.jp. 2 Present address: Graduate School of Bioagricultural Sciences, Nagoya University, Nagoya 464-8601, Japan.…”
mentioning
confidence: 99%